Corporate investor confidence in the aftermath of a mega natural disaster: An empirical study of the 2008 Wenchuan earthquake. (May 2020) - Wang, Ao; Marinova, Dora; Wang, Fei; Wei, Jiuchang
Highlights: Disaster distance consists of geographical distance and temporal distance. Investors have more confidence in firms with farther disaster distance from the big earthquake. The relationship between disaster distance and investor confidence would diminish as firm performance advances. The relationship between disaster distance and investor confidence would amplify as industry risk advances. Abstract: Previous studies show that extreme disasters, such as earthquakes, have enormous impacts on individual and organizational behavior, including self-protection. While such experience is important for risk control processes, the influence of disasters on corporate performance and stakeholder perceptions, especially that of investors, has not yet been investigated. Investment behavior however is a key factor in the recovery process. How the corporate world reacts after a disaster is an indicator for the renewal and revival ability of the affected economies and their long-term sustainability. This study contributes to understanding post-disaster corporate investor confidence by investigating how the distance from the severely affected area influences corporate investor confidence. By analyzing 98 publicly listed companies located in the disaster areas of the 2008 Wenchuan earthquake, the analysis finds that during 2008–2013 both geographical and temporal distances serve as promoters in influencing the post-disaster investor confidence. Moderating effects of firm performance and industry risk on the relationship between disaster distance and post-disaster investor confidence are identified. The paper also outlines possible future research directions.